2007
DOI: 10.1111/j.1440-1673.2007.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐radiofrequency ablation syndrome after percutaneous radiofrequency of abdominal tumours: One centre experience and review of published works

Abstract: The aim of this study was to evaluate prospectively post-radiofrequency ablation (RFA) syndrome and to determine its effect on the quality of life in the 15 days after percutaneous RFA treatment. We carried out an internal review board-approved prospective study of the delayed symptoms that occurred after 71 consecutive RFA sessions in 53 patients (12 women and 41 men; age range 45-83 years; mean age 71.6 years) with 45 primary liver tumours, 34 liver metastases, 3 renal cell carcinoma (RCC), 2 residual lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 33 publications
2
26
0
5
Order By: Relevance
“…A relatively common anticipated side effect following percutaneous RF ablation of abdominal tumors is known as postablation syndrome, which includes low-grade fever (37.5°-38.5°C), delayed pain, nausea, vomiting, malaise, and myalgias ( 77 ). In a retrospective review by Carrafi ello et al ( 77 ), postablation syndrome was observed in 32% of 53 patients who had undergone percutaneous ablation of an abdominal tumor.…”
Section: Side Effects and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively common anticipated side effect following percutaneous RF ablation of abdominal tumors is known as postablation syndrome, which includes low-grade fever (37.5°-38.5°C), delayed pain, nausea, vomiting, malaise, and myalgias ( 77 ). In a retrospective review by Carrafi ello et al ( 77 ), postablation syndrome was observed in 32% of 53 patients who had undergone percutaneous ablation of an abdominal tumor.…”
Section: Side Effects and Complicationsmentioning
confidence: 99%
“…In a retrospective review by Carrafi ello et al ( 77 ), postablation syndrome was observed in 32% of 53 patients who had undergone percutaneous ablation of an abdominal tumor. These symptoms are notable for being self-limited, responding well to acetaminophen or nonsteroidal antiinfl ammatory agents, and otherwise requiring no procedural intervention ( 78 ).…”
Section: Side Effects and Complicationsmentioning
confidence: 99%
“…La tecnologia delle microonde (MW) è un trattamento ablativo relativamente nuovo applicabile a differenti tipologie di neoplasie, in grado di offrire tutti i benefici della radiofrequenza, presentando inoltre sostanziali vantaggi, quali: volumi di necrosi cellulare più ampi, riduzione del tempo di procedura, maggiori temperature alla lesione target, possibilità di utilizzare multiple antenne simultaneamente, efficacia su lesioni con componente cistica e/o in prossimità di strutture vascolari >3 mm di diametro con riduzione dell'heat sink effect, minore dolore intraprocedurale [5,6,[13][14][15][16][17][18][19][20][21][22].…”
Section: Patientsunclassified
“…It is able to offer all the benefits of RFA as well as some substantial advantages. These include larger volumes of cellular necrosis, reduced procedure times, greater temperatures delivered to the target lesion, the possibility of the simultaneous use of multiple antennae, efficacy on lesions with cystic components and/or in proximity to vascular structures >3 mm in diameter with a reduction in the heat-sink effect, and less intraprocedural pain [5,6,[13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang et al [52] demonstrated comparable results for MWA and RFA with regard to overall survival, local progression, and the degree of local tumor ablation for HCC < 3 cm [52] . Additionally, MWA shows the same frequency of post-ablation syndrome, i.e., occurrence of low-grade fever, nausea, vomiting, malaise, and postinterventional pain [53] as RFA [54] . In an actual multicenter study, Groeschl et al [55] demonstrated excellent complete tumor ablation rates of approximately 94% as assessed by histology after resection of the respective pre-treated tumors, with a reported median recurrencefree survival of 25 mo.…”
Section: Mwamentioning
confidence: 99%